Kepemimpinan Perempuan dalam Menghadapi Konflik Organisasi dari Perspektif Komunikasi - Yarnis, Yarnis; Swarnawati, Aminah; Yusuf, Alfiyah Syadza; Sari, Sinta Purnama (Koneksi, 2024)
Efforts to deal with conflict are one of the competencies that every leader should have, without exception, women leaders. This study aims to analyze how women as leaders overcome and face organizational problems and examine women's communication styles in conflict management. Further study is critical because more and more women are leaders in strategic sectors of organizations such as the Ministry of Finance held by Sri Mulyani and the Ministry of Foreign Affairs under Retno Marsudi. The analysis uses concepts contained in the natural characteristics of women as leaders that were studied by Kanter in 1977 by adapting to the concept of communication theory presented by Wayne R. Pace. The method of data analysis is carried out with a descriptive analysis approach by reviewing existing literature on organizational conflict, which is reinforced by the validity of data from credible literature. The results of this analysis are expected to be a reference for leaders in organizations to be selective in determining women to become prospective leaders in the organization. In addition, it is a reference for women leaders who already exist in the organization in terms of behaving and acting when dealing with conflict. Upaya menghadapi konflik merupakan salah satu kompetensi yang patut dimiliki setiap pemimpin tanpa terkecuali pemimpin perempuan. Penelitian ini bertujuan untuk menganalisis cara perempuan sebagai seorang pemimpin dalam mengatasi dan menghadapi masalah pada organisasi, serta mengkaji gaya komunikasi perempuan dalam manajemen konflik dalam organisasi. Pentingnya kajian lebih lanjut dilakukan karena sudah semakin banyak perempuan yang menjadi pemimpin pada organisasi-organisasi di sektor strategis seperti Kementerian Keuangan yang dipegang oleh Sri Mulyani dan Kementerian Luar Negeri yang berada di bawah Retno Marsudi. Analisis menggunakan konsep yang termuat pada karakterisik alamiah perempuan sebagai pemimpin yang sudah dikaji oleh Kanter pada 1977 dengan menyadurkan pada konsep teori komunikasi yang disampaikan oleh Wayne R. Pace. Metode analisis data dilakukan dengan pendekatan analisis desktiptif dengan mengkaji literatur yang sudah ada mengenai konflik organisasi yang diperkuat dengan keabsahan data dari literatur yang memiliki kredibilitas. Hasil dari analisis ini diharapkan bisa menjadi acuan bagi para pemimpin di organisasi bisa selektif dalam menentukan perempuan untuk menjadi calon pemimpin dalam organisasi. Selain itu sebagai referensi bagi pemimpin perempuan yang sudah ada di organisasi dalam bersikap dan bertindak dalam menghadapi konflik.